Walory i produkt turystyczny euroregionu Neisse-Nisa-Nysa w opinii odwiedzających go turystów - Jaremen, Daria E.; Jedlińska, Maja; Nawrocka, Elżbieta (Advantages and the Neisse-Nisa-Nysa Euroregion Tourist Product According to Opinions of Visiting Tourists, 2005)
Tourists visiting three parts of the Neisse-Nisa-Nysa Euroregion become a valuable information source regarding the level of tourist offer for this region. Such knowledge is acquired on the basis of direct contacts with tourists, both in the form of conversations, interviews or more formal survey studies. Being aware of the reasons for which visitors have selected this region as the place for their holiday stay and the advantages of the tourist product which they prefer, the upgrading of offered services may follow. Despite the generally positive attitude of tourists towards the advantages and tourist management of the Euroregion, there can be observed certain gaps both in the field of tourist information, in the marking of attractions, advertising events' schedule or modernising infrastructure elements. Elimination of these gaps may create a chance for an increase in tourist traffic in the Neisse-Nisa-Nysa Euroregion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 69-92